PEMBELAJARAN SENI BUDAYA DAN KETERAMPILAN DENGAN KOMPETENSI DASAR MENYANYIKAN LAGU SECARA UNISONO PADA SISWA KELAS V DI SDN 09 AIR TAWAR BARAT - Ramadanti, Retno; Lumbantoruan, Jagar; Hadi, Harisnal (SENDRATASIK UNP, 2019)
AbstractÂ The article aims to find out and describe the implementation of learning cultural arts and skills, especially learning music in SDN 09 Air Tawar Barat. The type of research was qualitative with using descriptive analysis methods. The object of research was the students and the teacher of grade V in SD Negeri 09 Air Tawar Barat. Data was obtained through several steps such as observation, interview, documentation, and literature study. The fact in learning, especially singing unisono in SD Negeri 09 Air Tawar Barat that the teacher still too focuses on the lecture method, the teacher needs to develop the exploration process by providing information about intonation, breathing, posture and expression in unisono singing firstly, elaboration in the form of building agreements through cooperative, collaboration and confirmation activity in the form of motivating and strengthening learning for the achievement of learning outcomes. The teacher does not have a careful planning, learning strategies, approaches and methods that have not been effective yet. The ability of students in singing unisono are still below average, this is due to the lack of guided exercises conducted by the teacher so that the students who have good musical talent become less thrive.Â Keywords: cultural arts skill, basic competence, Unisono